Influência dos fatores motivacionais no desempenho de estudantes do curso de Ciências Contábeis: um estudo multicaso sob a perspectiva da teoria da autodeterminação - Schnell, Maico (2017)
The objective of the study was to know how the different stages of motivation / demotivation influence the performance of the students of the course of Accounting Sciences of a private and a public institution, according to the Theory of Self-determination. A sample of 261 respondents from the questionnaires structured based on the Academic Motivation Scale (EMA) was selected, and also had the participation of 25 interviewees, considering the three dimensions of intrinsic, extrinsic motivation and demotivation, presented by the Self-Determination Theory (Deci and Ryan, 1985). The collected data were analyzed with software SPSS 20 and Atlas.TI 7.0, through descriptive analysis and content analysis. The results showed that there are differences between the factors that generate the academic motivation among the students of Private and Public HEI. Beginning students of IES Private are more motivated extrinsically by identification, presenting as a preponderant factor, that university education will increase their competence as a professional, while the final students are more motivated by external control. The students of the Public HEI are more motivated extrinsically by external control, being the factors preponderant, in order to have a good remuneration in the future and, for the final students, was in order to obtain a prestigious job in the future. Regarding the types of motivation / demotivation and academic performance, the students oriented by intrinsic motivation presented themselves with the highest self-perception of performance among the students starting and finishing the HEI Private. In the public IES, the intrinsically motivated beginner students are the ones with the highest performance self-perception score, except for the final students in whom the self-perception score was higher among those motivated extrinsically, that is, there are differences between the factors that generate motivation / demotivation and self-perception of performance among beginners and undergraduates and between private and public HEI. Thus, the study concluded that students recognize that they are protagonists in the training process, therefore, responsible for the quality of learning, failing to transfer responsibility to courses, HEI and teachers. Finally, it is believed that the results of this study can contribute to the improvement of teaching and research in the Public and Private HEI courses in public and private HEIs, as well as teaching and research in other areas.